New species of Narnia (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini) from Mexico and key to the known species of the genus - Brailovsky, Harry; Barrera, Ernesto (Zootaxa, 2013)
One new species of Narnia is described from Mexico, N. anaticula sp. nov. A key to the species is provided together with dorsal view photograph of each known species of Narnia. The genus is divided in two groups according the color of the dorsal abdominal segments.